Late-stage trifluoromethylthiolation of benzylic C-H bonds - Xu, Wentao (Nat Commun, 2019)
The benzylic positions in drugs are sites that readily react with cytochrome P450 oxidases via single-electron oxidation. New synthetic methodologies to incorporate a fluoroalkyl group at the benzylic site are continually being developed, and in this paper, we report a metal-free and site-selective organophotoredox-catalyzed trifluoromethylthiolation of benzylic C-H bonds for a wide variety of alkyl arenes and heteroarenes. The precise and predictive regioselectivity among various C(sp(3))-H bonds originates from an inner-sphere benzylic radical initiation mechanism, and avoids the use of external oxidants or hydrogen atom abstractors. Its practicality stems from the trifluoromethylthiolation of a series of drugs and complex organic molecules, which is overwhelmingly selective for benzyl groups. This operationally simple protocol can provide a general and practical access to structurally diverse benzylic trifluoromethyl sulfides produced from ubiquitous benzylic C-H bonds. Large scale trifluoromethylthiolation can be achieved with continuous flow photoredox technology.